Cycle Optimization on Reheat Adsorption Cycle Applying Fixed Chilled Water Outlet Temperature. Issue 7 (23rd May 2016) - Bagus Wirajati, I Gusti Agung; Ueda, Yuki; Akisawa, Atsushi; Miyazaki, Takahiko
Abstract : This study investigated the cycle optimization of four-bed, silica gel–water adsorption with reheat cycle, where the desorber (upper bed) and adsorber (lower bed) always interact with the condenser and evaporator, to exploit a low heat-source temperature. In a previous study, the performance of a reheat cycle with chilled water outlet temperature fixed at 9°C was observed without considering the cycle optimization. Maintaining a constant chilled water outlet temperature is also of equal importance to improve the conversion efficiency so that maximum cooling capacity can be derived. In this paper, a simulation model of reheat adsorption cycles is developed to analyze the optimization of the cycle time, including adsorption/desorption time, mass recovery time, and preheating/precooling time, with chilled water outlet temperature fixed. The reheat working principle is also introduced. The proposed cycle is compared with the four-bed versison without reheat cycle in terms of coefficient of performance (COP) and cooling capacity. The result shows that the performance of a reheat cycle is superior to that of four-bed version without reheat, especially for low heat-source temperature. For low heat-source temperature (55–65°C) both COP and cooling capacity of the reheat cycle with optimization were raised significantly compared to the high heat-source temperature (70–80°C).